Targeting regulation of stem cell exosomes: Exploring novel strategies for aseptic loosening of joint prosthesis - Ma, Tian-Liang; Chen, Jing-Xian; Ke, Zhuo-Ran; Zhu, Peng; Hu, Yi-He; Xie, Jie (Frontiers in Bioengineering and Biotechnology, 2022)
Periprosthetic osteolysis is a major long-term complication of total joint replacement. A series of biological reactions caused by the interaction of wear particles at the prosthesis bone interface and surrounding bone tissue cells after artificial joint replacement are vital reasons for aseptic loosening. Disorder of bone metabolism and aseptic inflammation induced by wear particles are involved in the occurrence and development of aseptic loosening of the prosthesis. Promoting osteogenesis and angiogenesis, mediating osteoclast and inflammation may be beneficial to prevent aseptic loosening of the prosthesis. Current research about the prevention and treatment of aseptic loosening of prosthesis focuses on drug, gene, and stem cell therapy and has not yet achieved satisfactory clinical efficacy or has not been used in clinical practice. Exosomes are a kind of typical extracellular vehicles (EVs). In recent years, stem cell exosomes have been widely used to regulate bone metabolism, block inflammation, and have broad application prospects in tissue repair and cell therapy.